Analysis of antiviral use efficiency criteria in the complex pharmacotherapy of community acquired pneumonia - S. O. Soloviov; I. V. Dziublyk; V. V. Trokhymchuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
According to modern view, bacterial pathogens are the leading and most common cause of community-acquired pneumonia (CAP), but at the same time the results of numerous microbiological studies conducted in recent years showed that viruses confidently play the next leading role of CAP causes. Today, antiviral therapy is successfully used within the complex therapy of respiratory diseases, which allows reduction of the disease severity and minimizes the risk of complications. The main requirements for the antiviral drug are fully responsive to the new antiviral drug vitaglutam, the active component of which is pentanedioic acid imidazolyl ethanamide, is a low molecular weight compound, an analogue of the natural peptidoamine. The aim of the work. Mathematical modeling and analysis of clinical and laboratory indicators dynamics of CAP with additional antiviral pharmacotherapy based on pentanedioic acid imidazolyl ethanamide. In the study, it was used retrospective data of 106 patients with mild form of CAP of viral and bacterial etiology. Patients were randomly divided into two groups. In the 1st main group (50 patients), antibacterial therapy was combined with the antiviral drug vitaglutam. Analysis of antiviral therapy efficiency was provided by grouping of patients and determination of their distribution by gradations of clinical and laboratory indicators, as well as the construction of a mathematical model of their dynamics. According to modeling results, the rate of body temperature normalization, which was higher in patients taking vitaglutam, was a clear criterion for the efficiency of antiviral therapy. With additional antiviral therapy, the dynamics of sputum in the lungs was less intense. Positive clinical changes were accompanied by an improvement in the clinical blood analysis indicators, namely, more significant was the dynamics of ESR decrease. At the same time, dynamics of leukocytes number in patients' blood was approximately the same in both groups. Analysis of dynamics of clinical and laboratory indicators using the proposed mathematical model suggests that additional prescription of vitaglutam to empirical stepwise antibiotic therapy can significantly reduce the time to achieve clinical and laboratory results of treatment of patients with CAP of viral and bacterial etiology.